2016
DOI: 10.1007/s10682-015-9796-1
|View full text |Cite
|
Sign up to set email alerts
|

Cultural niche construction of repertoire size and learning strategies in songbirds

Abstract: Birdsong is a complex cultural and biological system, and the selective forces driving evolutionary changes in aspects of song learning vary considerably among species. The extent to which repertoire size, the number of syllables or song types sung by a bird, is subject to sexual selection is unknown, and studies to date have provided inconsistent evidence. Here, we propose that selection pressure on the size and complexity of birdsong repertoires may facilitate the construction of a niche in which learning, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 101 publications
(105 reference statements)
1
23
0
Order By: Relevance
“…For example, social learning has been extensively studied in nonhuman animals, in which behavioral strategies, such as producer and scrounger, and cultural trajectories can be more clearly defined than in humans (166,179). Cultural transmission also has large-scale evolutionary implications for some nonhuman animals: For example, theoretical studies suggest that nonrandom mating in birds based on culturally transmitted songs could accelerate speciation (180,181) and that sexual selection on learned songs could influence evolution of the neural underpinnings of learning (182). Recently, studies in a range of animal species have shown that cultural practices can emerge, spread, and change over time, potentially influencing individuals' fitness (183)(184)(185)(186)(187).…”
Section: Discussionmentioning
confidence: 99%
“…For example, social learning has been extensively studied in nonhuman animals, in which behavioral strategies, such as producer and scrounger, and cultural trajectories can be more clearly defined than in humans (166,179). Cultural transmission also has large-scale evolutionary implications for some nonhuman animals: For example, theoretical studies suggest that nonrandom mating in birds based on culturally transmitted songs could accelerate speciation (180,181) and that sexual selection on learned songs could influence evolution of the neural underpinnings of learning (182). Recently, studies in a range of animal species have shown that cultural practices can emerge, spread, and change over time, potentially influencing individuals' fitness (183)(184)(185)(186)(187).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that open‐ended learners would be more likely to show a correlation between individual song elaboration and reproductive success than closed‐ended learners, because open‐ended learners could potentially signal their age with their song. Extending the song‐learning window is expected to be metabolically costly (Beecher & Brenowitz, ; Creanza, Fogarty, & Feldman, ), so longer learning windows should be present only in species where there is selection for song traits that could benefit from extended learning windows, such as sexual selection for larger individual repertoires. Indeed, it has been suggested that adult song learning is associated with the evolution of larger repertoires (Creanza et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Extending the song‐learning window is expected to be metabolically costly (Beecher & Brenowitz, ; Creanza, Fogarty, & Feldman, ), so longer learning windows should be present only in species where there is selection for song traits that could benefit from extended learning windows, such as sexual selection for larger individual repertoires. Indeed, it has been suggested that adult song learning is associated with the evolution of larger repertoires (Creanza et al, ). However, we found that the strength of this correlation in species with plastic songs was not significantly different than in song‐stable species.…”
Section: Discussionmentioning
confidence: 99%
“…There is also recent evidence relating structural changes in the human brain to Paleolithic tool-making abilities (27,28), but additional work is still needed to clarify the direction of causation between culture and cognition (we will return to discuss these findings toward the end of the paper). Finally, when animal culture is considered, a recent study (29) suggests an effect of culture on learning in songbirds: a larger repertoire size is found in species that developed open-ended learning ability.…”
mentioning
confidence: 99%